137 - THE PRESENCE OF HUMAN ERROR IN SERVICE TO REHABILITATION OF THE UNIFIED HEALTH SYSTEM (Fiep Bulletin - online, 2011)
The rehabilitation center of Assis Gurgacz School (FAG) has been operating since 2006 as a service of high complexity in rehabilitation, through the Unified Health System (SUS) in the city of Cascavel, Paraná, given the population with rehabilitation and the dispensation prostheses. This research aimed to identify the perceptions of users of the public in relation to the prosthesis received and see how is the dispensation of prostheses and rehabilitation of users, whereas there is human error in the formulation of rules and ordinances that control center rehabilitation. We interviewed 51 amputees, between 20/09/2009 to 15/10/2009, chosen randomly. According to the results we observed that 75% of users made the process of adaptation to the prosthesis, and 67% are adapted to it. The sample was also found that 78% of users use the prosthesis daily. With regard to user feedback regarding the hearing, it was found that 4% of users reported that it is bad, which is 24% regular, 62% believe that the hearing is good and 10% qualified as great a prosthesis. The views of users in relation to the rehabilitation center's observations showed that 6% consider regular, 61% good and 33% felt that the rehabilitation center is great. The results of this study can be seen that most users have a good sense of hearing and offered rehabilitation, but omesmo also suggested that there are problems that could be solved by better control of human error.
Keywords: Human Error; Prosthesis; Rehabilitation